The Relationship Between Eating Pattern and Macronutrient Intake With The Incidence Of Hypertension Against The Elderly In The Neighbourhood 01 Wonokromo Village Surabaya - Daniel Julianto Sugeng; Rahayu Dewi Soeyono (Healthy-Mu Journal, 2023)
Individuals who have entered the elderly are vulnerable to disease, one of the diseases often suffered is hypertension. Hypertension is a silent killer where the symptoms are various in each individual and are almost the same as other diseases. Eating pattern and macronutrient intake have an important contribution towards the occurrence of hypertension. This study aims to determine the relationship between eating pattern and macronutrient intake with the incidence of hypertension in the elderly at neighbourhood 01 Wonokromo Village, Surabaya. This study is a quantitative study with a cross sectional approach. Respondents used were 50 people who live in neighbourhood 01 Wonokromo Village, Surabaya using the total sampling method. The instruments used were the Semi Quantitative Food Frequency Questionnaire (SQ-FFQ) and a valid and reliable eating pattern questionnaire. The relationship was analyzed using Rank Spearman test. The results showed that there was a relationship between eating pattern and the incidence of hypertension (P=0.0002) and there was no significant relationship between carbohydrate nutrients and the incidence of hypertension (P=0.479) while macronutrients protein (P=0.0004) and fat (P=0.002) had a significant relationship with the incidence of hypertension. Based on these results it can be concluded that there is a relationship between eating pattern and macronutrient intake of protein and fat with the incidence of hypertension against elderly in neighbourhood 01 Wonokromo Village, Surabaya.